MANET security appraisal: Challenges, essentials, attacks, countermeasures & future directions - Olanrewaju, Rashidah Funke; Khan, Burhan Ul Islam; Anwar, Farhat; Pampori, Bisma Rasool; Naaz Mir, Roohie (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2020)
Currently, Mobile Ad hoc Networks (MANETs) have evolved as one of the essential next-generation wireless network technologies. MANET comprises of mobile nodes that are self-configurable, and every mobile node behaves as a router for every other node allowing data to move by making use of multi-hop network routes. MANETs signify a networking class that is crucial and differs from conventional systems. Although MANETs are being popularly employed in commercial as well as academic fields, these were primarily designed for deployment in areas like military battlefields, emergency rescue and search operations, and other challenging or hostile environments. The distributed and wireless nature of MANETs paves the way for intruders to reduce MANET functionalities. MANET are susceptible to various attack at different layers since the majority of MANET routing protocols are designed with the assumption that no malicious intruder is present in the network. Therefore, recognizing those threats and finding solutions for their mitigation become essential. This study analyses various security attributes, challenges, attacks on multiple layers and countermeasures for thwarting attacks in MANETs